Design Based-Learning of Learning Management System (LMS) With Moodle to Improve Independence and Science Learning Outcomes of Junior High School Students - Napitupulu, Jernita Yohana; Simanjuntak, Mariati Purnama (Universitas Negeri Semarang, 2022)
This study aims to determine the design of learning media based on learning management system (LMS) with Moodle can increase independence and science learning outcomes for junior high school students. The design of the designed learning media can be used as an alternative in distance learning because it can be done without space and time limits. This type of research is research and development (R&D). The sample used in this study was class VII-4 totaling 23 students. The research instrument used consisted of two, a questionnaire and a test. Questionnaires to measure student learning independence and tests to measure student learning outcomes. The test used is in the form of multiple choice with 4 options that have been validated by experts. The relationship between independence and student learning outcomes using the Pearson product moment correlation test assisted by IBM version 25. Based on the results of the study, it was found that the LMS-based learning media design with Moodle can increase student independence and learning outcomes and there is a positive relationship between independence and student learning outcomes in junior high school Negeri 6 Percut Sei Tuan, Medan.